2017
DOI: 10.1155/2017/6178358
|View full text |Cite
|
Sign up to set email alerts
|

Yinchen Linggui Zhugan Decoction Ameliorates Nonalcoholic Fatty Liver Disease in Rats by Regulating the Nrf2/ARE Signaling Pathway

Abstract: Yinchen Linggui Zhugan Decoction (YCLGZGD) is the combination of Linggui Zhugan (LGZGD) and Yinchenhao (YCHD) decoctions, two famous traditional Chinese medicine prescriptions. In previous studies, we found that Yinchen Linggui Zhugan Decoction (YCLGZGD) could regulate lipid metabolism disorder and attenuate inflammation in pathological process of nonalcoholic fatty liver disease (NAFLD). However, the exact underlying mechanism remains unknown. The aim of this study was to explore the effect of Yinchen Linggui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Therefore, reduction of Nrf2 may make cells less sensitive to oxidative stress. Growing investigations have drawn attention to the alteration of Nrf2ARE feedback loop in counteracting the progression of various liver disorders including viral hepatitis, cirrhosis, hepatocellular carcinoma, and nonalcoholic liver disease [ 164 , 165 , 166 , 167 ]. Furthermore, this feedback loop associates with liver regeneration, as well.…”
Section: Network Pharmacology-associated Studymentioning
confidence: 99%
“…Therefore, reduction of Nrf2 may make cells less sensitive to oxidative stress. Growing investigations have drawn attention to the alteration of Nrf2ARE feedback loop in counteracting the progression of various liver disorders including viral hepatitis, cirrhosis, hepatocellular carcinoma, and nonalcoholic liver disease [ 164 , 165 , 166 , 167 ]. Furthermore, this feedback loop associates with liver regeneration, as well.…”
Section: Network Pharmacology-associated Studymentioning
confidence: 99%
“… 2013 ; Guo et al. 2017 ). However, little is known about the expression of Nrf2/Keap1 in the testes of animals with NAFLD or after C. aronia treatment, which were examined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yinchen Wuling San decoction presented a favorable outcome in liver cirrhosis from a large cohort study in southwest China [ 9 ]. Another study indicated that Yinchen Linggui Zhugan decoction ameliorates nonalcoholic fatty liver disease in rat by regulating the Nrf2/ARE signaling pathway [ 10 ]. However, the underlying mechanism between Yinchen and liver disease remains investigation.…”
Section: Introductionmentioning
confidence: 99%